Inovasi Penyusunan Paket Wisata sebagai Upaya Pengembangan Desa Wisata di Kecamatan Paciran Kabupaten Lamongan - Zuhriyah, Iffah Nur Halimatuz; Mijiarto, Joko (VISA: Journal of Vision and Ideas, 2024)
Paciran has a diversity of potential attractions in terms of tourism, history, and culture that are inherent in each tourist village. However, despite the diversity there are still undeveloped tourist attractions that are less exposed, so there is a need to optimize the potential of these attractions. Like the Tourism and Culture Department of Lamongan District's initiative to support the 2021-2026 RPJMD in developing integrated tourism potential. The aim of this research is to map the potential of tourist attractiveness and to compile the innovation of tourism village development in Paciran Emergency through the elaboration of integrated tour packages. This study employs a descriptive-qualitative approach. In this study, primary data sources are obtained from informants, as well as secondary data resources from supporting documents. This study uses Miles and Huberman's analysis techniques for data analysis, which includes data collection, data reduction, data presentation, and conclusion drawings. The results of the research showed that the concept of developing tourist villages through the innovation of package preparation for tourism in an integrated way between tourism villages in Paciran district was an attempt to create interesting tourist products by optimizing potential tourist attractiveness. There are three types of potential tourist attractions identified among other attractions of nature, culture, and artificial tourism. Innovation tour packages are structured into three kinds: (1) Enjoy the Goddess of Paciran, (2) Explore the Goddess of Paciran, and (3) Edu Ceria Goddess Paciran, each of which is sold at a price that varies according to the calculation of the cost components contained in it. It is hoped that the latest innovation efforts can be carried out in a sustainable manner, with the aim of providing an update to every tour package product offered to tourists.